STRATEGI PEMASARAN UNTUK MENINGKATKAN JUMLAH KUNJUNGAN WISATA DI KOTA MAKASSAR - Hikmah, Hikmah; Nurdin, Nurdin (COMPETITIVENESS, 2018)
Abstract Makassar is rich in tourist attractions, ranging from historical, maritime, to culinary tourism. To increase the attraction, the Makassar City Government continues to improve. Makassar city has a variety of tourist attractions that are so beautiful and fun to be visited by tourists from various regions and foreign countries. First, a destination development program. Second, pogram tourism marketing development, namely the implementation of destination promotion or introducing tourism Makassar City to be worth visiting by providing information about existing destinations in the city of Makassar and other supporting facilities that are packed well and the implementation of fixed annual events that are scheduled and other supporting events of quality so as to increase the attractiveness of tourists of the archipelago and local and mancanagera, such as the Losari Festival , Makassar expo, Makassar culinary, dragon boat festival, folk game festival, jazz festival Fort Rotterdam, Makassar marathon, anging mammiri art performance, international writers festival, international seascreen and many more events carried out by the government and other parties in various forms of activities in the field of performing arts, sports, education and health and other things that are held annually in the city of Makassar.  Keywords: Strategy, Marketing, Visits, Tourists, Makassar.  ABSTRAK Makassar kaya akan objek wisata, mulai dari wisata sejarah, bahari, hingga kuliner. Untuk meningkatkan daya tarik objek wisata itu, Pemerintah Kota Makassar terus berbenah. Kota Makassar memiliki beragam daya tarik wisata yang begitu indah dan menyenangkan untuk dikunjungi oleh para wisatawan dari berbagai daerah dan negara asing. Pertama, program pengembangan destinasi. Kedua, pogram pengembangan pemasaran pariwisata,yaitu pelaksanaan promosi destinasi atau memperkenalkan kepariwisataan Kota Makassar untuk layak dikunjungi dengan memberikan informasi mengenai destinasi yang ada di Kota Makassar dan fasilitas pendukung lainnya yang dikemas dengan baik dan pelaksanaan event tahunan tetap yang terjadual serta event-event pendukung lainnya yang berkualitas sehingga dapat meningkatkan daya tarik wisatawan nusantara maupun lokal serta mancanagera, seperti Festival Losari, Makassar expo, Makassar culinary, dragon boat festival, festival permainan rakyat, festival music jazz Fort Rotterdam, Makassar marathon, pentas seni anging mammiri, festival writers internasional, international seascreen dan masih banyak lagi event yang dilaksanakan pemerintah maupun pihak lain dalam berbagai macam bentuk kegiatan dalam bidang seni pertunjukan, olah raga, pendidikan maupun kesehatan dan hal lain yang setiap tahunnya dilaksanakan di Kota Makassar.  Kata Kunci : Strategi, Pemasaran, Kunjungan, Wisatawan, Makassar.